Asexual Recombinants of Plasmopara halstedii Pathotypes from Dual Infection of Sunflower. - Otmar Spring; Reinhard Zipper (PLoS ONE, 2016)
Genetically homogenous strains of Plasmopara halstedii differing in host specificity and fungicide tolerance were used to test the hypothesis that asexual genetic recombination occurs and may account for the high genotype diversity of this homothallic reproducing oomycete, which causes downy mildew in sunflower. Dual inoculation of sunflower seedlings with single zoospore strains of complementary infection characteristics caused sporulation under conditions where inoculation with each strain alone failed to infect. PCR-based investigation with strain-specific primers proved the presence of genetic traits from both progenitors in single sporangia collected from sporangiophores of such infections. Sister zoospores released from these sporangia revealed the genotype of the one or the other parental strain thus indicating heterokaryology of sporangia. Moreover, some zoospores showed amplification products of both parents, which suggests that the generally mononucleic spores derived from genetic recombination. The possibility of parasexual genetic exchange in the host-independent stage of infection and the evolutionary consequences are discussed.